Pedagogical aspects of optimization of pre-start readiness of highly qualified sicks on the baidark and Сanoe (Journal of Educational Sciences, 2018)
The article examines the problem of researching the state of readiness of highly skilled oarsmen inthe pre-competition stage and the competitive period. The study is aimed at comparing the studiedconditions in oarsmen. The main of them we chose the need for communication, inner well-being, externalactivity and sportive attitude. The solution of this problem can be realized with a comprehensivestudy and the ability to manage the conditions of oarsmen in their preparation and performances incompetitions. Rowers with high levels of preparedness are more likely to perform predictable results.We consider the readiness status of oarsmen specializing in kayak and canoe, with different typologicalproperties. Diagnostics of the level of their condition in the period of responsible competitions will allowcreating typological standards intended for assessing the condition of the oarsmen’s organism.Key words: optimization, pre-statistical readiness, highly qualified sticks, kayaks, canoe, pre-competitionstage, competition period.